Apelin Regulates Nuclear Factor-κB's Involvement in the Inflammatory Response of Pancreatitis. Issue 1 (January 2017) - Han, Song; Englander, Ella W.; Gomez, Guillermo A.; Greeley, George H.
Abstract : Objectives: Inflammation plays a key role in pancreatitis. Earlier studies from our laboratory showed that experimental pancreatitis activated the pancreatic apelin-APJ axis robustly in mice. Apelin signaling reduced neutrophil invasion and the activation of pancreatic nuclear factor (NF)-κB in mice with experimental pancreatitis. Methods: The aim of this study was to assess whether apelin-induced inhibition of pancreatic NF-κB activation was linked mechanistically to apelin's inhibition of pancreatic inflammatory mediator up-regulation in mice with cerulein-induced chronic pancreatitis (CP). Whether apelin's inhibitory effects were associated with the inhibition of NF-κB binding to the promoter region of IL-1β was examined. The effects of apelin exposure on pancreatic IκB degradation/replenishment and membrane levels of phosphorylated protein kinase C were measured. Results: Results demonstrated that apelin inhibited the up-regulation of pancreatic tumor necrosis factor α, macrophage inflammatory protein-1 α/β, and IL-1β expression significantly in mice with CP. Chromatin immunoprecipitation assay findings showed that apelin inhibited NF-κB binding to a putative NF-κB binding site in the IL-1β promoter. Apelin exposure reduced the pancreatic membrane levels of phosphorylated protein kinase C-δ and enhanced the replenishment of pancreatic IκB proteins. Conclusions: Together, these findings indicated that the inhibition of NF-κB activation by apelin was a mechanism behind the reduced pancreatic levels of inflammatory mediators in CP mice exposed to apelin.